Dislocation distribution and patterning in 〈a〉-axis Mg single crystals during early compression. (1st February 2019) - Niewczas, M.; Kula, A.; Kitahara, H.; Ando, S.
Abstract: Dislocation distribution and patterning during the onset of uniaxial compression of 〈 a 〉 -axis Mg single crystals was investigated by transmission electron microscopy (TEM) and etch-pitting technique. The crystals deform by dislocation glide using basal and nonbasal slip systems. The high hardening rate Θ ≈ E / 50 − E / 30 indicates the effective forest hardening by nonbasal dislocations observed in the microstructure. Distribution of dislocation etch-pits shows the polygonized arrangement of dislocations along the basal plane. TEM observations reveal the heterogeneous structure of dislocations clustered in dense arrays surrounded by dislocation free areas. Dislocation arrangements that are building blocks of the microstructure include monopoles, dipoles, multipoles, ribbons, walls, bundles, and braids. The patterns are characterized with respect to their dislocation content and spatial distribution. They fall into the category of low energy structures, which favorite the configurations reducing the elastic energy of the arrays. The degree of interactions between basal and 〈 c + a 〉 slip systems is attributed to playing a key role in the formation of observed dislocation arrangements. Graphical abstract: Image 1